Current trend in tourism (trends in camping and outdoor hospitality) / Shaiful Bahri Siswanto - Siswanto, Shaiful Bahri (2017)
Tourism industry is one of the fast and emerging industry which brings a big impact towards the industry. This industry has become a common worldwide leisure activity that has risen and is accessible to a greater division of the global population. This write up will specify the current trends in tourism industry such as camping and outdoor hospitality. The impact towards the industry are also highlighted in this writing. Firstly, camping industry is where tourists get involved with the nature and makes camping as a medium for them to stay replacing other accommodation like hotel, hostel etc. This industry comes with inexpensive accommodation. What is highlighted in this topic is about the changes and trends that emerged from the camping industry and also the RE-trend that can make to the camping industry if the demand reduce and to make sure the camping have a place in market. Second, about the outdoor hospitality. These sector includes Recreational Vehicles (RV), caravan, and etc. outdoor hospitality served the user with a mobile accommodation where the user will not have have to stay in a hotel. They can travel and stay in their vehicles at the same time. I will highlight about the various classes of vehicles that tourist can choose and the RV Park, with the kind of facilities are that provided to the user. Lastly, I will highlight the positive impact of camping industry and outdoor hospitality towards the industry itself. Camping and outdoor hospitality are increasing because of the demand from tourists after the innovation of camping but they still lack in research and not much information that any writers can collect.